Pengaruh Organisasi Kemahasiswaan Terhadap Belajar Mahasiswa Difakultas Sains Dan Teknologi - Harefa, Titus Felix Fulito; Waruwu, Stanley Yeremia (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Student activity in organizations plays an important role in developing knowledge and preparing them to enter the world of work. Through organizations, students are accustomed to conveying thoughts and ideas that can increase self-confidence and motivation to learn, which has a positive impact on academic achievement. This research aims to examine the role of student organizations in supporting student abilities, using descriptive methods. The research sample consisted of 10 students from the 2022/2023 information technology study program. The research results show that there is a significant influence between student involvement in student organizations on their learning achievement. Student organizations provide opportunities for students to develop their talents, interests and potential through productive, creative and practical activities carried out on campus, for example extracurricular activities, which in turn increase motivation and academic achievement. In addition, involvement in an organization can shape character, skills, self-confidence, as well as expand knowledge, insight and social networks. This research also reveals that students are involved in organizations not only for existence or popularity, but as a form of self-actualization. Therefore, it is recommended that the campus, such as the Deputy Chair III for Student Affairs and Study Programs, provide further support to encourage student organization activities that can improve student achievement. Overall, this research shows that involvement in student organizations has a significant positive relationship with learning motivation, which influences academic quality and preparation for the world of work.